2016
DOI: 10.1016/j.jaci.2016.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase and tensin homolog ( PTEN ) mutation can cause activated phosphatidylinositol 3-kinase δ syndrome–like immunodeficiency

Abstract: PTEN loss-of-function mutations can cause APDS-like immunodeficiency because of aberrant PI3K pathway activation in lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
77
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 30 publications
10
77
0
Order By: Relevance
“…Although the CD19 + B220 − B cells we describe resemble B1 cells by some criteria, such as the expression of CD5 and CD43, their lower IgM expression, lack of B220 and distribution pattern suggest that they are related but distinct to conventional B1 and B10 cells 30, 31 . A similar subset has previously been described as being dependent on CD19 and increased in the absence of PTEN expression and PTEN haploinsuffiency in humans can lead to an APDS-like syndrome 3840 .…”
Section: Discussionsupporting
confidence: 58%
“…Although the CD19 + B220 − B cells we describe resemble B1 cells by some criteria, such as the expression of CD5 and CD43, their lower IgM expression, lack of B220 and distribution pattern suggest that they are related but distinct to conventional B1 and B10 cells 30, 31 . A similar subset has previously been described as being dependent on CD19 and increased in the absence of PTEN expression and PTEN haploinsuffiency in humans can lead to an APDS-like syndrome 3840 .…”
Section: Discussionsupporting
confidence: 58%
“…Here we use the generic term APDS unless referring specifically to either. A milder form of APDS-like immunodeficiency has been described in Cowden disease, caused by heterozygous loss of PTEN, although the increases in PIP 3 and pAKT levels from these patient T cells was less obvious than observed in the T cells from patients with APDS69, 75.…”
Section: Alterations In Pi3kδ Signalling Leads To Pids In Humansmentioning
confidence: 84%
“…Subsequently, a number of additional studies have identified APDS patients with mutations in PIK3CD 5, 7, 6469 or PIK3R1 6, 7073. Patients with GOF mutations in either of these genes appear to largely phenocopy each other, despite the fact that p85α is ubiquitously expressed and can pair with p110α and p110β in addition to p110δ.…”
Section: Alterations In Pi3kδ Signalling Leads To Pids In Humansmentioning
confidence: 99%
“…In general, MTORC1 regulates cell autonomous growth by controlling nutrient availability and growth factors, whereas MTORC2 mediates cell proliferation and survival by regulating cell surface area (45,49). Dysregulation of upstream signals, such as PI3K/AKT mutation (50), Phosphatase and tensin homolog (PTEN) mutation (51), Tuberous sclerosis complex (TSC) loss of function (52), and RAS mutation (53), often results in the alteration of MTOR, which has been demonstrated to contribute to a poor prognosis in serious cancers including NSCLC, breast cancer, gastric cancer and esophageal squamous cell carcinoma (5457). The activation of MTOR is mediated by Ser2448 phosphorylation through the PI3K/AKT/MTOR pathway, and then it activates a potent oncogene, EIF4E (58).…”
Section: Discussionmentioning
confidence: 99%